A sensitive LC-ESI-MS/MS method for the determination of clotrimazole in human plasma. Issue 16 (21st August 2015) - Zhou, Rui; Tang, Fang; Li, Sanwang; Xie, Xiang; Peng, Jie; Xie, Feifan; Mu, Lingli; Yu, Peng
<x xml:space="preserve">Abstract</x> A systematic validation of a sensitive and rapid LC-ESI-MS/MS assay for the determination of clotrimazole in human plasma was developed for the first time.